Co‐frequency Interference Suppression for Aerostat Passive Bistatic Radar. Issue 3 (1st May 2018) - Wang, Feng; Wei, Shuang; Jiang, Defu
Abstract : Co‐frequency interference is frequently encountered in the aerostat passive bistatic radar exploiting frequency modulated broadcasting signals. Independent component analysis (ICA) in frequency domain, one of the classic Blind source separation (BSS) algorithms, is utilized to recover the direct signal in the above scenarios. To solve the permutation problem of the frequency domain BSS, we use the method of correlation in time‐frequency domain between the output of ICA and the coarse reference signal achieved by pattern synthesis with nulls in the direction of the interference or reference stations. In order to suppress the interferences and clutters, the separated direct signals of the reference and interference broadcasting signals are fed into a type of two dimensional adaptive filters in space and fast temporal domain. The processing scheme shows good performance in target detection, which is validated by computer simulation.